Antirrhinum majus L. flower extract inhibits cell growth and metastatic properties in human colon and lung cancer cell lines. Issue 11 (1st October 2020) - Seo, Jina; Lee, Jungjae; Yang, Hyi Young; Ju, Jihyeung
Abstract: Snapdragon ( Antirrhinum majus L.) flowers are one of the most frequently used edible flowers in different preparations of foods and drinks. In this study, we examined inhibitory effects of snapdragon flower extract (SFE) against distinctive properties of cancer cells, stimulated growth, and activated metastasis, using H1299 lung cancer and HCT116 colon cancer cell lines. SFE treatment at 100–1, 000 μg/ml for 24–72 hr resulted in a time‐ and dose‐dependent growth inhibition in H1299 and HCT116 cells. Cell cycle analysis and Annexin V staining assay further revealed that SFE caused cell cycle arrest at G2/M phase and induction of apoptosis, indicating the growth inhibition by SFE is attributed to its G2/M cell cycle‐arresting and apoptosis‐inducing activities. SFE dose‐dependently enhanced generation of intracellular reactive oxygen species (ROS) and reduced mitochondrial membrane potential in H1299 cells but had no effect on intracellular ROS levels in HCT116 cells, suggesting that the type of apoptosis induced by SFE in H1299 cells is different to that in HCT116 cells. Furthermore, SFE alleviated invasion, levels of matrix metalloproteinases, migration, and adhesion in H1299 and HCT116 cells. These results indicate that SFE not only inhibits cell growth by cell cycle arrest at G2/M and apoptosis induction but also alleviates metastatic properties such as invasion, migration, and adhesion in lung and colon cancer cells. Abstract : Snapdragon flower extract not only inhibits cell growth by cell cycle arrest at G2/M phase and induction of apoptosis but also alleviates metastatic properties such as invasion, migration, and adhesion in human lung and colon cancer cells.